Between viewing and experiencing - Adams, Margaret, author; Gravdahl, John, advisor; Coke, Pamela K., committee member; Faris, Suzanne, committee member; Moseman, Eleanor F., committee member (Colorado State University. Libraries, 2018)
Psychologist, American philosopher, and educational reformer John Dewey, once said, "Give the pupils something to do, not something to learn; and the doing is of such a nature as to demand thinking; learning naturally results." We learn through play and exploration. As an observer and participant in this world, my own personal experiences inadvertently impact me as a maker, and as a teacher. This is a continual revolving influence. My experiences, my artwork, and my teaching all have a direct impact on each other. There are intersecting connections and overlapping interests between design as visual communications and teaching. They are about shared experiences and both encompass communication, personal expression, collaboration, transmission of information, participation, and interpretation. Design and teaching are about communication. Design can communicate a message in different ways such as through typography, visuals, materials, color, symbolism, etc. What we know as a viewer by experience, impacts our interpretation of the artwork. We look for ways to relate to the artwork based on what we know. The artwork can push us into feeling uncomfortable to promote a concept or a message. Even though an artist may have a specific message in mind, there is no check system to ensure the viewer received that message. In the classroom, I aim to create a comfortable environment for students to encourage a safe place for interactive learning. There are checks and balances in place, such as quizzes, tests, discussions, projects, and critiques to ensure the message that was presented was clearly understood. If a student does not understand the message that was communicated, they can be affected since the message deepens the understanding of the industry they are preparing to enter as well as techniques that are needed to be a successful designer. Artwork is different, the message could be passive or ambiguous. It could be meant to engage and stir up a reaction. Art is between object and viewer; the collaboration is personal and internal. Teaching is a collaboration between teacher and student, it is external. With teaching, collaborating with students relies on student experiences to grasp the concepts being communicating. With art, collaboration depends on the object or art to start the discussion, whereas with teaching the focus is on the teacher to start the discussion. Design and teaching can be static or interactive but collaboration is always present. Design can encourage critical thinking, reaction, and even a change in the viewer's thinking. In my role as a teacher, I aim to encourage critical thinking. For example, I give a prompt and I expect students to come back with a concept for their project. They are acting and reacting to the direction they are given. I encourage change in their own thinking as we move through the semester and they learn new industry skills. As an artist, my artwork does the same. If I design a poster for a theater concert to promote sale tickets, my goal is to encourage viewer participation by convincing them to purchase tickets. I never questioned whether graphic design was a form of art, but in graduate school, I came to the realization that teaching is an art form and there is an unquestionable connection between design and teaching. As an artist, I explore concepts through sketching and digital exploration. Through this process, the concept develops. As a direct result, I grow as an artist, learning and expanding my knowledge and experience. As I choose materials, size, typography, and visuals for my artwork, I am framing a message. As a teacher, I play the same role. I choose the message I wish to convey to my students, and frame the presentation through a selection of materials, typography, and visuals. I have come to the realization that teaching a design class and creating artwork have many commonalities. In the classroom, I am creating an experience for the students–they are the viewers and what I am participating in is a creative act. Many disciplines grade student knowledge and understanding my asking multiple choice questions. As a design teacher, I can ask multiple choice questions when it comes to industry terms and basic design knowledge, but design as a visual communication encompasses so much more. Technique, content, and concepts must also be evaluated and that cannot be done through multiple choice questions. I must handle students individually in a studio setting, grasping what individuals are getting and not getting from the instructions based on the work they are creating. I must be able to think on my feet and change gears quickly relying on my own intuition of the design field. Teaching is a creative act the same way making artwork is.
Keywords: graphic design